Application of a Chairside Anaerobic Culture Test for Endodontic Treatment - Masahiro Yoneda; Seidai Kita; Nao Suzuki; Sonia M. Macedo; Kosaku Iha; Takao Hirofuji (International Journal of Dentistry)
Periapical lesions are caused by bacterial infections. The fundamental objective of endodontic treatment is to eliminate bacteria present in the root canal system because they play an important role in the development and maintenance of periapical lesions. Therefore, confirming the absence of bacteria before filling root canals is important. Anaerobic culture tests have been used in many endodontic cases, and they have brought about good treatment outcomes. These tests, however, require specific apparatuses and bacteriological techniques. Here, we report a chairside anaerobic culture test that does not require any specialized apparatuses or techniques. We also report two endodontic cases in which this simple test was used. Both patients were diagnosed with chronic purulent periapical lesions. After confirming the absence of bacteria in the root canals, they were filled with gutta-percha points. At followup, the radiolucencies showed recovery, although longterm observation is under way. From these results, the authors conclude that this simple chairside anaerobic culture test is effective for evaluating periapical lesion treatment procedures.